Cost Budget Analysis for Equal Distribution of Labour for Multi-Storey Buildings Construction - Dewanty, Maharani Putri; Putra, I Nyoman Dita Pahang (Indonesian Journal Publisher, 2024)
Although all resources on a construction project have their respective roles, the availability of labour significantly impacts how far the project moves forward and is completed. According to Kastor and Sirakoulis (2009), calculating the number of workers according to the construction schedule is crucial because, without this consideration, the resulting schedule may not be effective and efficient. process used for construction project resources to reduce fluctuations (Waluyo & Aditama, 2017). This research compares labour allocation, duration, and labour wage cost budgets under several conditions. These conditions include actual project conditions, planning, and results after levelling using an auto schedule. In project planning, the fluctuations obtained are pretty sharp. After the auto schedule levelling, the manpower no longer experienced overallocation, but fluctuations between weeks were still relatively high. This can happen because the quantity of work and labour in the construction projects under review is not comparable to the effects of project delays. The results obtained from the comparisons analyzed on the X-storey building construction project are that the auto schedule does not change the initial planning duration, which remains at 133 days. There was a disparity of 0.02% in auto schedule planning costs from 1,098,345,000.00. Meanwhile, in actual conditions, the labour cost budget increased by 0.12% from IDR 967,880,000.00 after the auto-schedule levelling process. It can be concluded that before resource levelling is carried out, it is necessary to review project scheduling and accelerate the duration of implementation, specifically if construction projects experience delays and other factors, so as not to cause fluctuations caused by the uneven quantity of work over some time.